Digital Futures : Living in a Networked World. - Wilsdon, James (Earthscan, 2001)
Beyond the hype about dot-coms WAP phones and dot-com entrepreneurs what impacts will e-commerce have on society? How will it affect jobs and local communities? What will it mean for the environment - for energy use transport and the future shape of our cities? How can we ensure that everyone enjoys the benefits of the new digital technologies? This is a groundbreaking exploration of the social and environmental impacts and opportunities of the new economy. It brings together the leading thinkers and visionaries from the worlds of policy business and academia in an insightful vigorous and at t.